2021
DOI: 10.1002/cssc.202102538
|View full text |Cite
|
Sign up to set email alerts
|

Methylation with Dimethyl Carbonate/Dimethyl Sulfide Mixtures: An Integrated Process without Addition of Acid/Base and Formation of Residual Salts

Abstract: Dimethyl sulfide, a major byproduct of the Kraft pulping process, was used as an inexpensive and sustainable catalyst/ co-reagent (methyl donor) for various methylations with dimethyl carbonate (as both reagent and solvent), which afforded excellent yields of O-methylated phenols and benzoic acids, and mono-C-methylated arylacetonitriles. Furthermore, these products could be isolated using a remarkably straightforward workup and purification procedure, realized by dimethyl sulfide's neutral and distillable nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…4 ). This substrate was chosen because it can easily be produced from guaiacol ( 54 ), one of lignin’s main depolymerization products ( 55 ). The obtained product veratric acid ( 6 ) represents an important feedstock for pharmaceutical industry, for example, in the synthesis of the gastrointestinal drug itopride ( 56 ) and has antioxidant and anti-inflammatory activities itself ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). This substrate was chosen because it can easily be produced from guaiacol ( 54 ), one of lignin’s main depolymerization products ( 55 ). The obtained product veratric acid ( 6 ) represents an important feedstock for pharmaceutical industry, for example, in the synthesis of the gastrointestinal drug itopride ( 56 ) and has antioxidant and anti-inflammatory activities itself ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Differently substituted phenols, benzoic acids and arylacetonitrile substrates were selectively methylated applying this protocol (22 examples, yields up to > 99 %). 98 Li et al reported the first example of a phosgene-free, two-step sustainable methodology for the synthesis of carboxylic anhydrides (NCAs) from γ-benzyl-Lglutamate (BLG) and DMC, upon initial formation of the Nmethoxycarbonyl-γ-benzyl-L-glutamate intermediate (NOM-BLG, 84 % yield) followed by intramolecular cyclization to give NCA-BLG in 67 % yield. 99 In the last 5 years, DMC was the main DACs employed in chemical valorisation of bio-derived platform chemicals, developing novel effective and sustainable methylation protocols accessing both aromatic platform chemicals and/or valuable renewable based monomers (e.g.…”
Section: An Archetype For Sustainable Reactions: Synthesis Of Glycero...mentioning
confidence: 99%
“…Differently substituted phenols, benzoic acids and arylacetonitrile substrates were selectively methylated applying this protocol (22 examples, yields up to >99%). 98 Li et al reported the first example of a phosgene-free, two-step sustainable methodology for the synthesis of carboxylic anhydrides (NCAs) from γ-benzyl- l -glutamate (BLG) and DMC, upon initial formation of the N -methoxycarbonyl-γ-benzyl- l -glutamate intermediate (NOM-BLG, 84% yield) followed by intramolecular cyclization to give NCA-BLG in 67% yield. 99…”
Section: Valorization Of Renewable-based Molecules and Platform Chemi...mentioning
confidence: 99%
“…[24] Methylation can also modify the solubility of drug molecules and improve the off-target selective as well. [25] The popular alkylation reagents, including alkyl halides, [26] dimethyl sulfates, [27] alkyl sulfonates [28,29] have been restricted for their environmental toxicity, potential danger to health and/or genotoxicity. [30][31][32][33][34] Safe and effective reagents are still in limited supply.…”
Section: Introductionmentioning
confidence: 99%